Asymmetric impact of fossil fuel and renewable energy consumption on economic growth: A nonlinear technique. (1st July 2021) - Baz, Khan; Cheng, Jinhua; Xu, Deyi; Abbas, Khizar; Ali, Imad; Ali, Hashmat; Fang, Chuandi
Abstract: Harnessing energy resources contributes to achieving economic targets and environmental change, as well as fulfilling energy demands via producing clean energy and new technologies. However, the procedures for accomplishing these interlinked objectives and achieving sustainable development need to be addressed empirically. To this end, we examined the nexus between fossil fuel, renewable energy, and economic growth, using a time series data 1980–2017 of Pakistan. By employing a non-linear autoregressive distributed lag and asymmetric causality approaches, this study determines the asymmetric impact of one variable on the others. During the investigation, the results confirmed asymmetric and nonlinear co-integration between pairs of the variables. An asymmetric feedback causality was observed between positive shocks to economic growth and renewable energy consumption. In contrast, the asymmetric causality test showed that positive and negative shocks in fossil fuel and economic growth had a neutral effect, while a symmetric bidirectional hypothesis was observed between fossil fuel consumption and economic growth. Finally, an asymmetrically unidirectional causal nexus was confirmed between foreign direct investment and economic growth. Prospectively, our findings suggest the significance of clean energy along with the installation of new technologies for achieving sustainable economic growth without undermining environmental intactness and ecosystem. Highlights: Asymmetric nexus between fossil fuel, renewable energy use and economic growth. Variables are decomposed into positive and negative shocks to examine nonlinearity. NARDL model is used to investigate long and short-run cointegration in one model. Asymmetric causality tests used to examine the nexus between the variables.